Potencjał twórczy uczniów w projektach edukacyjnych - Kasprzak , Michalina (Studia Edukacyjne, 2023)
Creativity is seen as one of the prerequisites for success in various areas of life. Students often look for additional activities outside school or university to help validate the knowledge and skills they have acquired. Through participation in educational projects (local and international), students gain extra-curricular knowledge, experience, and competences, but are only sometimes able to put these into practice on their own to create new ideas, concepts, or solutions. The article presents the process of supporting and developing students’ creative potential on the example of selected educational projects.